PENGELOLAAN PEMBELAJARAN PUISI MELALUI PENDEKATAN KOMUNIKATIF DAN CTL PADA SISWA SD - Sudir Sudir Sudir (Manajer Pendididikan, 2016)
The purpose of this study was to reveal the contents read poetry. In learning basic competence is in sixth grade at SDN 05 Kepahiang the author, only 33,33% who achieved mastery learning. This research is done by using the communicative approach and the application of Contextual Teaching Learning in learning management as on effort to improve students abilityto reflect recited poems. Outcomes since cycle I showed an increase until the second cycle, no more students don’t pass the study even 2 students (8,33%) gained value in the range of 86-90 scores. Besides, the students feel that learning becomes fun and can develop the imagination, sharpen the sensitivity of emotion, educate and hone language skills.Keywords: communicative, CTL, poetry, language, management